Communicating Fashion Trend Research and Forecasting - Goncu Berk, Gozde; DeLong, Marilyn (Open textbook library., 2023)
Communicating Fashion offers a holistic view of the interrelationships involved in trend research, including data collection, analysis and reporting, and forecasting what that direction means for design. The book’s primary focus is on the process of observing and collecting desk and field data to understand interrelationships among products, user experience, and contextual factors.